Slips of the Tongue in EFL Spoken Production: A Multilingual Analysis Across Age, Gender, and Speech Setting - Rohi Qimmahtum; Nurenzia Yannuar; Zen, Evynurul Laily (Universitas Hamzanwadi, 2025)
EFL learners in Indonesia, who typically speak a local mother tongue and Bahasa Indonesia as the national language due to the country’s linguistic diversity, often face additional challenges when speaking English, classified as a foreign language, leading to an increased likelihood of slip-of-the-tongue (SOT) errors. This descriptive qualitative study aims to identify the types and frequencies of SOT produced by Indonesian multilingual speakers in EFL spoken production and to investigate whether SOT occurrence is influenced by age, gender, and speech settings (prepared vs. unprepared). Twelve participants were divided into two age groups (13–19 and 20–35), consisting of three males and three females. Data from recorded readings and interviews were transcribed and analyzed, revealing 250 total SOT occurrences. The findings show that all eight SOT types proposed by Caroll (2007) were present, with substitution as the most frequent (79 instances), followed by deletion (65), anticipation (36), perseveration (23), addition (20), exchange (15), and shift and blend as the least frequent (7 each). The 13–19-year-old group produced more SOTs overall than the 20–35-year-old group, while females produced more SOTs than males. Regarding speech settings, the younger group (13–19) generated more SOTs in prepared speech, whereas the older group (20–35) produced more unprepared speech. The prominence of specific SOT types suggests that future research should explore how juggling multiple linguistic systems shapes speech production and error patterns.